1999
DOI: 10.1046/j.1464-5491.1999.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral vitamin E (α‐tocopherol) supplementation on vascular endothelial function in Type 2 diabetes mellitus

Abstract: There may be receptor-specific endothelial dysfunction in subjects with uncomplicated Type 2 DM. This is not improved by treatment with alpha-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 55 publications
(72 reference statements)
6
98
0
3
Order By: Relevance
“…There is evidence in Type II diabetes for and against improvement in vasodilator function of forearm resistance arteries in response to the muscarinic agonist acetylcholine with vitamin E supplementation [10,11]. One positive study using a vitamin E analogue was not placebo controlled but did show reduction in plasma F 2 -isoprostanes in a small number of patients [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence in Type II diabetes for and against improvement in vasodilator function of forearm resistance arteries in response to the muscarinic agonist acetylcholine with vitamin E supplementation [10,11]. One positive study using a vitamin E analogue was not placebo controlled but did show reduction in plasma F 2 -isoprostanes in a small number of patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…One positive study using a vitamin E analogue was not placebo controlled but did show reduction in plasma F 2 -isoprostanes in a small number of patients [11]. Vitamin E supplementation was reported to improve forearm microcirculatory function in a larger sample of Type II diabetic patients in a well-controlled trial [10]. Improvement in methacholine-mediated vasodilator function of forearm resistance vessels was also reported in Type II diabetes following the intra-arterial administration of vitamin C [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the more limited contribution of NO to endothelium-dependent vasodilatation in these vessels. In the forearm circulation of patients with type II diabetes, vitamin E supplementation during 8 weeks did not improve endothelium-dependent vasodilatation (Gazis et al, 1999). Surprisingly, high dose vitamin E supplementation caused a further attenuation of endothelium-dependent vasodilatation in mesenteric arteries of the rat, despite a decrease of the 8-epi-prostaglandin F 2a level, an indicator of oxidative stress (Palmer et al, 1998a), suggesting that exaggerated antioxidant supplementation may even be deleterious.…”
Section: Aetiology Of Endothelial Dysfunction In Diabetesmentioning
confidence: 93%
“…Impaired ACh-induced relaxation with normal responses to bradykinin has been reported in isolated resistance vessels from patients with type I diabetes (McNally et al, 1994), in the forearm circulation of type II diabetes patients (Gazis et al, 1999) and in mesenteric and hindlimb arteries of streptozotocin (STZ)-rats (Lash & Bohlen, 1991;Taylor et al, 1995), suggesting an abnormality at the level of the G-proteins. However, several other studies found equally suppressed responses to di erent endothelium-dependent agonists (Heygate et al, 1995;Fulton et al, 1996;Costa e Forti & Fonteles, 1998;Mayhan & Patel, 1995;1998;Mayhan, 1997) or impaired relaxation to the calcium-ionophore A23187 (Oyama et al, 1986;Durante et al, 1988;Cameron & Cotter, 1992;Fukao et al, 1997), making a disturbance of receptors or receptor-coupled mechanisms unlikely as a common mechanism of endothelial dysfunction.…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 96%